2018
DOI: 10.1007/978-3-319-99707-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Models for Digitalization in Manufacturing - Applicability for SMEs

Abstract: Digitalization is a challenging topic for manufacturing SMEs. Besides improving their technological base, they have to keep the business offer attractive, e.g. by bundling their products with smart services. In addition to limited resources, often the necessary knowledge is missing to select the right technologies and develop attractive services based on their functionality. Due to the resulting high risks, SMEs neglect the chances of digitization and lose competitiveness. To start with, they need a maturity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 4 publications
0
22
0
2
Order By: Relevance
“…Similarly, Wiesner et al [38] review four maturity models with SMEs in consideration, with less emphasis on self-assessment as Brozzi et al [37]. Wiesner et al [38] conclude that the maturity models presented by Schumacher et al [39], Jarrahi et al [40], and Lichtblau et al [41] are simpler to apply and require less knowledge about Industry 4.0 for the companies themselves compared to the maturity index presented by Schuh et al [20]. However, However, the Industry 4.0 Maturity Index [20] was selected as a methodological foundation for this paper since it considers a more holistic approach including an emphasis on organizational issues, which is important when it comes to implementation of Industry 4.0 enabling technologies [11].…”
Section: Industry 40 Maturity Indexmentioning
confidence: 87%
See 2 more Smart Citations
“…Similarly, Wiesner et al [38] review four maturity models with SMEs in consideration, with less emphasis on self-assessment as Brozzi et al [37]. Wiesner et al [38] conclude that the maturity models presented by Schumacher et al [39], Jarrahi et al [40], and Lichtblau et al [41] are simpler to apply and require less knowledge about Industry 4.0 for the companies themselves compared to the maturity index presented by Schuh et al [20]. However, However, the Industry 4.0 Maturity Index [20] was selected as a methodological foundation for this paper since it considers a more holistic approach including an emphasis on organizational issues, which is important when it comes to implementation of Industry 4.0 enabling technologies [11].…”
Section: Industry 40 Maturity Indexmentioning
confidence: 87%
“…For evaluating the level of readiness or maturity towards implementing aspects of Industry 4.0, various assessment tools exist [37,38]. Brozzi et al [37] review ten of such self-assessment tools for SMEs and conclude that there is no one-size-fits-all solution.…”
Section: Industry 40 Maturity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…An uncertainty needs to be address in earlier stage [73]. An assessment model should clarify uncertainties rather than forming new ones [74]. Technological complexity in implementing smart manufacturing is not precisely defined [75].…”
Section: The Mental Model Of Smart Manufacturing Readiness Assessmentmentioning
confidence: 99%
“…Wiesner at al. [74] suggested that SMEs need a step-by-step guide to help them embrace the concept of Industry 4.0 and smart manufacturing. Therefore, focusing on the Man, Machine, Management, and Method will be the easiest thrust for the SMEs to perceive the journey of smart manufacturing.…”
Section: The Mental Model Of Smart Manufacturing Readiness Assessmentmentioning
confidence: 99%